Water Regime and Nitrogen Management to Cope with Wheat Yield Variability under the Mediterranean Conditions of Southern Portugal - Patanita, Manuel (2019)
Global climate change accentuates the seasonal and interannual irregularity of temperature and precipitation of the Mediterranean climate. The consequences of this variability on wheat production are felt on its development cycle and productivity, making the production chain of this crop vulnerable to the occurrence of years with abnormal distributions of precipitation and with extreme temperatures. Adaptation strategies like irrigation or fertilization can help to cope with the negative impacts of climate uncertainty. This study evaluated the effects of water regime and nitrogen (N) fertilization techniques on wheat production in southern Portugal based on the results of three trials conducted in two agricultural years (2016/2017 and 2017/2018) with contrasting climate conditions. Phenology and yield were evaluated by comparing water regimes (R1, full irrigation; R2, supplemental irrigation at four stages: start of stem extension, booting, anthesis, grain filling; R0, rainfed (in 2017/2018)) and N fertilization splitting/timing and type (conventional and enhanced effciency fertilizers (EEFs): controlled-release N, stabilized with nitrification inhibitor, and stabilized with urease inhibitor). Significant effects of water regime on grain yield were obtained in 2016/2017, a year with extreme aridity and high water requirements felt from the tillering stage, in the trial with conventional fertilizers. In 2017/2018, when a beneficial seasonal rainfall distribution occurred, water regime did not influence grain yield, pointing to the feasibility of supplementary irrigation to maximize water productivity. Nitrogen fertilization influenced yield and its components, with the highest values of grain yield being obtained with conventional fertilizer. Regardless of the possible effects on grain quality, the use of EEF did not prove to have an indisputable effect on wheat yield in the conditions under which the trials were conducted. Comparison of the results in the two years accentuates the need to continue the evaluation of the influence of agronomic management in wheat production in the context of adaptation to the climatic uncertainty in Mediterranean regions.